2009
DOI: 10.1007/s00421-009-1022-9
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory resistive loading after all-out exercise improves subsequent performance

Abstract: We have previously shown that post-exercise inspiratory resistive loading (IRL) reduces blood lactate ([Lac(b)(-)]). In this study, we tested the hypothesis that IRL during recovery could improve subsequent exercise performance. Eight healthy men underwent, on different days, two sequential 30-s, cycle ergometer Wingate tests. During the 10-min recovery period from test 1, subjects breathed freely or through an inspiratory resistance (15 cm H(2)O) with passive leg recovery. Arterialized [Lac(b)(-)] values, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
1
15
2
Order By: Relevance
“…In stark contrast to the findings of Chiappa et al (3,4), we observed no effect of ITL upon lactate recovery kinetics. The novel finding of this investigation is that following IMT, ITL accelerates the capacity for whole body lactate exchange and clearance.…”
Section: Paragraph Number 29contrasting
confidence: 99%
“…In stark contrast to the findings of Chiappa et al (3,4), we observed no effect of ITL upon lactate recovery kinetics. The novel finding of this investigation is that following IMT, ITL accelerates the capacity for whole body lactate exchange and clearance.…”
Section: Paragraph Number 29contrasting
confidence: 99%
“…Secondly, Chiappa et al (2009) showed that increasing the work of breathing (via pressure-threshold loading) during recovery from maximal exercise significantly accelerated rates of lactate clearance and improved subsequent 30 s maximal cycling performance. The authors suggest that with loading, the inspiratory muscles are capable of net lactate consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has emerged that respiratory muscle activity may strongly influence the systemic blood lactate concentration ([lac -] B ) (Brown et al 2008(Brown et al , 2010Chiappa et al 2009;Johnson et al 2006;Renggli et al 2008;Verges et al 2007). This notion contradicts the traditional view that the small mass of the respiratory muscles (estimated at around 960 g (Freedman et al 1983)) and their large oxidative capacity precludes any systemically relevant lactate exchange (Wetter and Dempsey 2000 Romer et al 2002b) and volitional isocapnic hyperpnoea training (endurance-training stimulus) (Leddy et al 2007;Spengler et al 1999), with up to 52% of variation in post-training whole-body exercise performance improvement accounted for by the reduced [lac -] B (Romer et al 2002b).…”
Section: Introductionmentioning
confidence: 99%
“…However, such effects have not been documented in humans thus far. The results of the cardiopulmonary exercise test performed here indicate that, despite carrying two TP53 mutant alleles, our patient has preserved functional capacity, as demonstrated by peak power output, peak oxygen uptake, and an anaerobic threshold within the limits of normality [21]. Moreover, ventilatory efficiency and hemodynamic responses to exercise were also normal.…”
Section: Discussionmentioning
confidence: 81%
“…The per minute ventilation/carbon dioxide output slope was calculated using a linear regression analysis based on all points of the incremental exercise [20]. Before and during the exercise tests, cardiac output and stroke volume were estimated non-invasively by impedance cardiography (PhysioFlow PF07 Enduro, Manatec Biomedical, Paris, France) as previously described [21]. Arterial oxygen saturation was measured by finger oximetry (Takaoka Oxicap, São Paulo, Brazil).…”
Section: Case Presentationmentioning
confidence: 99%